Teacher education and teaching for diversity: a call to action. Issue 2 (3rd April 2022) - Ryan, Mary; Rowan, Leonie; Lunn Brownlee, Jo; Bourke, Terri; L'Estrange, Lyra; Walker, Sue; Churchward, Peter
ABSTRACT: Teachers around the world report a lack of confidence about working with learners who are regarded as 'diverse'. This paper draws on mixed-methods research to explore knowledge claims that underpin the pedagogical work of teacher educators. Using our theoretical framing of epistemic reflexivity, we show connections between knowledge claims made across the broad literature of teacher education/diversity and those made by teacher educators about their practices and programs. Findings identified challenges with respect to existing practice which point to different ways of knowing about our work. This paper is a call to action for teacher educators to reclaim their accountability for teaching diversity.